2014
DOI: 10.1007/s00402-014-2049-x
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Broström repair with Gould augmentation via an accessory anterolateral port for lateral instability of the ankle

Abstract: Although several arthroscopic surgical techniques for the treatment of lateral instability of the ankle have been introduced recently, some concern remains over their procedural complexity, complications, and unclear clinical outcomes. We have simplified the arthroscopic technique of Broström repair with Gould augmentation. This technique requires only two small skin incisions for two ports (medial midline and accessory anterolateral ports), without needing a percutaneous procedure or extension of the skin inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(78 citation statements)
references
References 12 publications
1
77
0
Order By: Relevance
“…Recently, several authors have reported good results using an arthroscopy-assisted lateral ligament repair [ 1 , 5 7 , 12 , 14 , 15 , 18 ]. Most of them also attempted to reinforce the construct by using the IER but found that this was both technically difficult and added significant surgery time to the procedure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several authors have reported good results using an arthroscopy-assisted lateral ligament repair [ 1 , 5 7 , 12 , 14 , 15 , 18 ]. Most of them also attempted to reinforce the construct by using the IER but found that this was both technically difficult and added significant surgery time to the procedure [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is less trauma to the surrounding tissue than in the case of open surgery, which reduces postoperative pain and permits an early rehabilitation protocol, leading to a faster recovery. [3][4][5][6]8,10,11 Using only 2 arthroscopic portals limits synovial injury, which reduces the risk of excessive edema and avoids extensive adhesion formation. Moreover, arthroscopic visualization of the joint enables one to anatomically restore the course of the ATFL from its fibular to talar footprint.…”
Section: Discussionmentioning
confidence: 99%
“…They can be divided into 2 categories: ligament repair or ligament reconstruction using a tendon graft or transfer. [3][4][5][6][7][8][9][10][11][12] The surgical procedure should be selected based on the tissue quality determined during arthroscopic assessment of the ATFL remnant. 11,13 The aim of this article was to present an arthroscopic technique for all-inside ATFL repair that allows for restoration of the ankle joint stability in a minimally invasive way.…”
mentioning
confidence: 99%
“…• Poor ligament-tissue quality can be a limitation of the repair technique and reconstruction should be considered in these cases [7][8][9] .…”
Section: Pitfalls and Challengesmentioning
confidence: 99%